1967
DOI: 10.2172/4245065
|View full text |Cite
|
Sign up to set email alerts
|

Rabble: A Program for Computation of Resonance Absorption in Multiregion Reactor Cells.

Abstract: A method· of computing resonance absorption in either slab or circularized reactor cells is developed and used to write a FORTRAN program, RABBLE, for the CDC-3600. Since the method uses space-and lethargydependent slowing-down sources, the ·program is well suited for the computation of resonance absorption when the effects of overlapping between resonances is significant. The cell is divided into regions, and the energy range of interest is divided into extremely narrow groups. Regional reaction rates are obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1970
1970
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…So, the direct formulation of the spatially dependent effective crosssections for each ring region within the cylindrical fuel lump is a difficult task. For generation of the detailed effective cross-section data within the pellet, the more accurate resonance self-shielding methods such as subgroup method [5] or ultra-fine-group calculation method [4] are applied in general. These methods consider the detailed information of the spatial and energetic resonance self-shielding effects within each energy group, so it can directly treat the neutron balance within the pellet.…”
Section: New Derivation Of Multi-term Rational Equation For General Lmentioning
confidence: 99%
See 1 more Smart Citation
“…So, the direct formulation of the spatially dependent effective crosssections for each ring region within the cylindrical fuel lump is a difficult task. For generation of the detailed effective cross-section data within the pellet, the more accurate resonance self-shielding methods such as subgroup method [5] or ultra-fine-group calculation method [4] are applied in general. These methods consider the detailed information of the spatial and energetic resonance self-shielding effects within each energy group, so it can directly treat the neutron balance within the pellet.…”
Section: New Derivation Of Multi-term Rational Equation For General Lmentioning
confidence: 99%
“…In general, the resonance calculation method is classified into three categories [3], i.e. ultra-fine-group method [4], subgroup method [5] and Dancoff method [6] with equivalence theory [7]. The ultra-fine-group method gives an accurate effective cross-section, but has a limitation for the practical design applications of large and complicated geometries in the fuel assembly level because of the long computation time.…”
Section: Introductionmentioning
confidence: 99%
“…( 8 ) are inserted into Eq. ( 7 ) and upon truncation after the first two terms, i. e., by making the P, approximation, it is found that +zjl(u')pcj} #(u')du' * (10) Hereafter, the suffix concerning nuclear species will be suppressed for convenience.…”
Section: With ( 9 )mentioning
confidence: 99%
“…Using the property that Pg = e"^uPg_ 1 , we can obtain the following recursion relation: Equation 33 is written for a single material in a given region. Generalization to many materials and regions requires that Eq.…”
Section: Slowing-down Sourcementioning
confidence: 99%